The role of leadership in driving corporate social responsibility and innovation: insights from Serbian organizations - Vukonjanski Srdic, Jelena; Pavlovic, Katarina; Berić, Ivana (Serbian Journal of Management, 2026)
The objective of this study is to examine the impact of transformational and transactional leadership styles on Corporate Social Responsibility (CSR) and Organizational Innovation (OI) within Serbian organizations. Using responses from 204 employees across small and medium, domestic and foreign companies, the research explores how leadership behaviors influence CSR initiatives and innovative practices. Data were collected through an online survey using a structured questionnaire and analyzed in SPSS with descriptive statistics, reliability testing, and multiple regression to examine relationships. Stratified sampling was applied to ensure representation across company size and origin. Two hypotheses were tested and proven highlighting significant differences of this influence based on organizational size and origin, with transformational leadership proving more effective than transactional leadership as a predictor of CSR and OI outcomes. The research findings point to the importance of culturally aligned leadership approaches in fostering sustainable and innovative practices, offering valuable insights for leadership development in transitional economies.
Keywords: leadership; CSR; innovation; size; origin